Zerumbone, a Natural Cyclic Sesquiterpene of Zingiber zerumbet Smith, Attenuates Nonalcoholic Fatty Liver Disease in Hamsters Fed on High-Fat Diet. (9th October 2013) - Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Chia Ju; Liu, I-Min
Abstract : We investigated the effects of zerumbone, a natural cyclic sesquiterpene, on hepatic lipid metabolism in Syrian golden hamsters fed on high-fat diet (HFD). After being fed HFD for 2 weeks, hamsters were dosed orally with zerumbone (75, 150, and 300 mg kg −1 ) once daily for 8 weeks. After treatment with zerumbone, the plasma levels of total cholesterol (TC) and triglycerides (TGs) and the contents of TC and TG in hepatic tissue as well as homeostasis model assessment of insulin resistance were lowered, especially in the zerumbone-treated group (300 mg kg −1 ). Moreover, the histological evaluation of liver specimens demonstrated that the steatosis and inflammation in liver of zerumbone-treated groups were improved. Zerumbone exhibited the ability to decrease hepatic mRNA levels of sterol regulatory element-binding protein-1c and its lipogenic target genes, such as fatty acid synthase, acetyl-CoA carboxylase 1, and stearoyl-CoA desaturase 1. The hepatic mRNA expression of peroxisome proliferator-activated receptor α, together with its target genes including carnitine palmitoyl transferase-1, acyl-CoA oxidase, and acyl-CoA oxidase 1, was also upregulated by zerumbone. In conclusion, zerumbone improves insulin sensitivity, decreases lipogenesis, and increases lipid oxidation in the liver of HFD-fed hamsters, implying a potential application in the treatment of nonalcoholic fatty liver disease.